Nanoparticle- and microparticle-based delivery systems : encapsulation, protection and release of active compounds - McClements, David Julian (CRC Press, 2015)
"Nanoparticle and microparticle delivery systems are finding increasing application in the food, pharmaceutical, personal care, and other industries. These types of colloidal delivery systems were traditionally used in the food industry to encapsulate active ingredients designed to improve food quality and safety, such as flavors, colors, antioxidants, enzymes, and antimicrobials. More recently, they are finding increasing use to encapsulate bioactive components that may improve human health and well-being, such as vitamins, minerals, and nutraceuticals. A well-designed colloidal delivery system can be used to overcome many of the technical challenges normally associated with incorporation of these active ingredients into commercial food and beverage products. The purposes of this book are to provide a comprehensive review of the various types of colloidal delivery systems available for encapsulating active ingredients in the food and other industries and to highlight their relative advantages and limitations. Initially, a discussion of the numerous kinds of active ingredients that the food industry is interested in incorporating into their products is given, and challenges associated with their encapsulation, protection, and delivery are discussed. The physicochemical and mechanical methods available for manufacturing colloidal particles are then discussed, and the importance of designing particles for specific applications is highlighted. Separate chapters are devoted to the three major types of colloidal delivery systems available for encapsulating active ingredients in the food industry: surfactant-based, emulsion-based, and biopolymer-based"-- Provided by publisher.
Keywords: Food -- Biotechnology.; Transport theory.; Colloids.; Microencapsulation.; elektronické knihy; electronic books